Intraoperative pivot‐shift accelerometry combined with anesthesia improves the measure of rotatory knee instability in anterior cruciate ligament injury - Gastón Caracciolo; Roberto Yáñez; Rony Silvestre; Carlos De la Fuente; Héctor Zamorano; Alejandra Ossio; Lars Strömbäck; Sebastian Abusleme; Felipe P. Carpes (Journal of Experimental Orthopaedics, 2021)
Abstract Purpose The knee stiffness acquired following an Anterior Cruciate Ligament (ACL) injury might affect clinical knee tests, i.e., the pivot‐shift maneuver. In contrast, the motor effects of spinal anesthesia could favor the identification of rotatory knee deficiencies prior to ACL reconstruction. Hence, we hypothesized that the intra‐operative pivot‐shift maneuver under spinal anesthesia generates more acceleration in the lateral tibial plateau of patients with an injured ACL than without. Methods Seventy patients with unilateral and acute ACL rupture (62 men and 8 women, IKDC of 55.1 ± 13.8 pts) were assessed using the pivot‐shift maneuver before and after receiving spinal anesthesia. A triaxial accelerometer was attached to the skin between Gerdys’ tubercle and the anterior tuberosity to measure the subluxation and reduction phases. Mixed ANOVA and multiple comparisons were performed considering the anesthesia and leg as factors (alpha = 5%). Results We found a higher acceleration in the injured leg measured under anesthesia compared to without anesthesia (5.12 ± 1.56 m.s− 2 vs. 2.73 ± 1.19 m.s− 2, p < 0.001), and compared to the non‐injured leg (5.12 ± 1.56 m.s− 2 vs. 3.45 ± 1.35 m.s− 2, p < 0.001). There was a presence of significant interaction between leg and anesthesia conditions (p < 0.001). Conclusions The pivot‐shift maneuver performed under anesthesia identifies better rotatory instability than without anesthesia because testing the pivot‐shift without anesthesia underestimates the rotatory subluxation of the knee by an increased knee stiffness. Thus, testing under anesthesia provides a unique opportunity to determine the rotational instability prior to ACL reconstruction.